2017
DOI: 10.1002/pd.5167
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of renal blood flow and renal volume in normal fetuses and in fetuses with a solitary functioning kidney

Abstract: Low PSV RA might have a predictive value for diagnosing a nonfunctioning kidney in fetuses with a SFK. We demonstrated a higher PSV RA and larger renal volume in the SFK compared with healthy kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Assessment of the renal parenchyma and renal growth are the most important because they provide an estimate of renal functional reserve. Hindryckx et al 8 . found that the kidneys were larger in children with solitary renal function.…”
Section: Discussionmentioning
confidence: 98%
“…Assessment of the renal parenchyma and renal growth are the most important because they provide an estimate of renal functional reserve. Hindryckx et al 8 . found that the kidneys were larger in children with solitary renal function.…”
Section: Discussionmentioning
confidence: 98%
“…There are a limited number of studies investigating normal fetal renal artery blood flow, and most have small sample sizes, are cross-sectional in design and have heterogeneous inclusion and exclusion criteria making direct comparison difficult. [12][13][14][15][16][17] Some earlier studies showed that the PI decreased with increasing GA. 12,13 The study most similar to our study, in that it was a longitudinal design and used mixed effects modelling, also demonstrated that the RI and PI remained relatively unchanged throughout the pregnancy. 16 Other studies demonstrated similar findings; however, these were not longitudinal in design.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Some earlier studies showed that the PI decreased with increasing GA. 12,13 The study most similar to our study, in that it was a longitudinal design and used mixed effects modelling, also demonstrated that the RI and PI remained relatively unchanged throughout the pregnancy. 16 Other studies demonstrated similar findings; however, these were not longitudinal in design. 14,15 A study in 2015 reported longitudinal reference intervals for fetal renal arteries, however was not truly longitudinal as although the design was longitudinal, the data were not analysed as longitudinal data.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiological conditions, the kidney volume of patients who underwent unilateral nephrectomy signi cantly increased postoperatively [13]. Similarly, the volume of solitary functioning kidney was notably larger compared to that of healthy kidney [14]. The increase in kidney volume is to improve renal function to meet the needs of metabolism and toxin excretion.…”
Section: Sensitivity Analysismentioning
confidence: 99%